The business of social justice in Macau - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | As Macau rebuilds its post-pandemic economy, one could be forgiven for believing that the good life for all has arrived, as evidenced in the manifest opulence on display in its up-market shopping malls. However, this is not the case; social justice needs attention in Macau.

Linguistic and economic capital in Macau - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Macau wisely looks to mainland China, South-East Asia, and Portuguese-speaking countries, as part of its economic diversification. However, to be a player on the international stage and world-wide market, it must look wider, and, hence, the standard of English in Macau must improve dramatically and urgently.

Chatting about chatting - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Many employers in Macau expect their employees to have received higher education (HE). This returns to the endless question of what HE is for; is it for job knowledge and skills acquisition, attitude development, thinking abilities, creativity, problem solving, how to learn, or what? What and whose knowledge?

Sunshine and shadows - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | The recent euphoria over Macau’s economic resurrection should not mask the long-standing challenges facing its society and values. Sunshine creates shadows in which can lurk a range of pathologies.

Games of chance - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Here we are, back in full-throttle summer tourism in tiny Macau, with visitors galore, lines of tourist coaches everywhere, and the casinos back on course to welcome gamblers. However, gambling reaches much wider than Macau’s casinos.

Conditional internationalism in Macau - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Just when diversification is the name of the game in Macau, and with the manifold benefits of diversity that internationals can bring, how sensible is it to treat its international non-resident workers so poorly, and with lamentable transparency and accountability?

Dreaming of diversification - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Once upon a time there was a cockerel who succumbed to flattery when a wily fox told him that he had the most magnificent singing voice, especially when he sang with his eyes closed tightly.

Santa Claus is not coming to everyone in Macau - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Macau Business | December 2023 Keith Morrison – Author and educationist

A risky new year - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Despite the welcome optimism expressed at the government’s plans to resurrect Macau’s economy, its economic recovery will continue to suffer from having had the rug pulled from under its feet by the zero-Covid policy, however well intentioned.

Human capital investment outflanked by Macau's needs - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | As Macau strives to revive its post-pandemic economy and to reinject life into its ailing society, calls for investment in human capital resurface, alongside endless mantras of economic diversification which, for years, seem to have fallen on deaf ears, and together with plans for further infrastructure development and construction which have already turned Macau into a concrete jungle.

The international recruitment obstacle race in Macau - Morrison, Keith (Macau Business, 2023)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Macau’s development of international and tertiary sector industries is the watchword for its long-overdue diversification. Is Macau ready for this?